How to give your users the LIS services they want - Pantry, Sheila; Griffiths, Peter 1948- (Facet, 2009)
This title will help any library or information professional anywhere to take a fresh look at this area and to tackle it in their organization, so as to ensure that their users will always obtain exactly what they want.